PROFESSIONAL TRAINING OF PUBLIC SERVANTS AT THE REGIONAL LEVEL IN THE CONTEXT OF UKRAINE'S EUROPEAN INTEGRATION AND DIGITIZATION OF ADMINISTRATIVE PROCESSES (Coordinates of Public Administration, 2026)
The article, based on the analysis of modern scientific literature, regulatory and legal support for management activities, primarily at the regional level, It is shown that in the context of Ukraine's future European integration and active digitalization of management processes, professional training of civil servants and local government officials is of particular importance, at the same time, this process is significantly complicated by the Russian-Ukrainian war, which has been going on for almost twelve years; It is noted that the professional training of competitive, adaptive public servants to modern changes requires the introduction of new approaches and digital technologies into the educational process; In this regard, it is shown that recently, electronic digital learning, including mass online courses, virtual learning, and the introduction of cloud technologies, has been gaining increasing popularity (and demands on them) among public servants; It has been proven that modern public service requires the development of such qualities in civil servants and local government officials as independence, responsibility, organization, and the ability to realistically assess one's strengths and make informed management decisions, which is extremely important, primarily in the context of the legal regime of martial law, which will last in Ukraine at least until February 3, 2026; It has been found that professional training of public servants today is more personalized, mobile, accessible and flexible, which is extremely important under conditions of minimal costs - time, financial, human resources, since local government bodies and local self-government bodies today are characterized by a significant shortage of managerial personnel; It has been proven that professional training of public servants in the context of Ukraine's prospective European integration, decentralization of power, and digitalization of management processes is a critical factor in the success of the reform, primarily at the regional level.